2021
DOI: 10.1101/2021.08.18.456785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription factor-based transdifferentiation of human embryonic to trophoblast stem cells

Abstract: During the first week of development, human embryos form a blastocyst comprised of an inner cell mass and trophectoderm (TE) cells, the latter of which are progenitors of placental trophoblast. Here we investigated the expression of transcripts in the human TE from early to late blastocyst stages. We identified enrichment of transcription factors GATA2, GATA3, TFAP2C and KLF5 and characterised their protein expression dynamics across TE development. By inducible overexpression and mRNA transfection we determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
(218 reference statements)
0
2
0
Order By: Relevance
“…Here we have demonstrated that repressive chromatin pathways oppose trophoblast induction in naive hPSCs. We showed that PRC2-mediated H3K27me3 marks trophoblast regulators in naive hPSCs, including genes that are expressed in trophectoderm cells of human blastocysts and can promote trophoblast fate 4,[53][54][55] . By establishing that PRC2 is a lineage gatekeeper stabilizing the undifferentiated naive state, these findings overturn the current assumption that naive hPSCs are epigenetically unrestricted.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Here we have demonstrated that repressive chromatin pathways oppose trophoblast induction in naive hPSCs. We showed that PRC2-mediated H3K27me3 marks trophoblast regulators in naive hPSCs, including genes that are expressed in trophectoderm cells of human blastocysts and can promote trophoblast fate 4,[53][54][55] . By establishing that PRC2 is a lineage gatekeeper stabilizing the undifferentiated naive state, these findings overturn the current assumption that naive hPSCs are epigenetically unrestricted.…”
Section: Discussionmentioning
confidence: 93%
“…The unexpected presence of H3K27me3 at the promoters of key lineage regulators in naive hPSCs raises the possibility that PRC2-mediated H3K27me3 might oppose cell-fate specification in naive hPSCs. Several of the trophoblast factors marked by H3K27me3 in naive hPSCs are expressed at high levels in trophectoderm cells of human blastocysts and their enforced expression induces the trophoblast cell fate 4,[53][54][55] . Consequently, because naive hPSCs have the capacity to produce trophoblasts in vitro 6,[11][12][13][14] , we sought to use trophoblast differentiation as a cell model to investigate a potential role for H3K27me3 in controlling lineage induction in human naive pluripotency.…”
Section: Conserved and Species-specific Chromatin Featuresmentioning
confidence: 99%
“…Understanding the varied roles of TFAP2C also has implications for in vitro cell reprogramming as TFAP2C has been used to generate induced TSCs (iTSCs) lines in both human and mouse 43,79,80 . Notably, multiple studies in non-trophoblast contexts have reported that TFAP2C also promotes cell fate transitions.…”
Section: Discussionmentioning
confidence: 99%